Presentation and Explanation of the Lexemas "Education", "Ilm" in the English and Uzbek Annotated Dictionaries - Narmuratov Zayniddin Radjabovich (Genius Journals, 2023)
This article analyzes lexemes of education and science in English and Uzbek languages. The definitions given to the lexemes of education and science are analyzed with reference to the explanatory dictionaries of the two languages
Keywords: lexemes of education and science; lexemes of knowledge; dictionaries